Cervical cancer screening uptake: A randomized controlled trial assessing the effect of sending invitation letters to non-adherent women combined with sending their general practitioners a list of their non-adherent patients (study protocol) - Teigné, Delphine; Banaszuk, Anne-Sophie; Grimault, Charlotte; Abes, Linda; Gaultier, Aurélie; Rat, Cédric (Frontiers in Public Health, 2022)
Introduction Cervical cancer (CC) is the fourth most common cancer among women. It can be cured if diagnosed at an early stage and treated promptly. The World Health Organization suggests that 70% of women should be screened with a high-performance test by the age of 35. This paper reports a protocol to assess the effect of two modalities of organized CC screening programmes on CC screening uptake. Methods and analysis Design and setting: The design involves a 3-arm randomized controlled study performed in a French geographic area on the west coast. A total of 1,395 general practitioners will be randomized, depending on their general practice surgeries. Participants: The design is based on a total of 94,393 women aged 40 to 65 years who are eligible for CC screening. Intervention: In the “optimized cancer screening” group, the intervention will combine sending invitation letters to non-adherent women with sending general practitioners (GPs) a list of their non-adherent patients. In the “standard cancer screening” group, the intervention will be limited to sending invitation letters to non-adherent women. In the “usual care” group, no letter will be sent either to women or to their GPs. Primary endpoint: CC screening test uptake will be assessed after a 6-month follow-up period. Statistical analysis: The percentage of women who are up-to-date with their screening at 6 months after the intervention will be compared across arms using a generalized mixed linear model. Discussion A large-scale randomized trial of this nature is unprecedented. The study will enable us to assess a strategy relying on GPs, identified as the coordinators in this screening strategy. The study results should help policy makers to implement organized CC screening programs in the future. Ethics and dissemination The study was approved was approved by the Ethics Committee of the National College of Teaching General practitioners (IRB00010804). It was recorded in ClinicalTrials.gov on the number NCT04689178 (28 December 2020). The study findings will be used for publication in peer-reviewed scientific journals and presentations in scientific meetings.